Tax evasion and measurement error: An econometric analysis of survey data linked with tax records - Alari Paulus (University of Essex, Institute for Social and Economic Research (ISER), 2015)
We use income survey data linked with tax records at the individual level for Estonia to estimate the determinants and extent of income tax compliance in a novel way. Unlike earlier studies attributing income discrepancies between such data sources either to tax evasion or survey measurement error, we model these processes jointly. Focussing on employment income, the key identifying assumption made is that people working in public sector cannot evade taxes. The results indicate a number of socio-demographic and labour market characteristics, which are associated with non-compliance. Overall, people in the bottom and the top part of earnings distribution evade much more and about 12% of wages and salaries in total are underreported, which is very substantial for a major income source subject to third party reporting and tax withholding.
Keywords: D31; H26; H31; 330; tax compliance; measurement error; linked data; Estonia